Plant volatile-triggered defense in citrus against biotic stressors - Pérez-Hedo, Meritxell; Gallego-Giraldo, Carolina; Forner-Giner, María Ángeles; Ortells-Fabra, Raúl; Urbaneja, Alberto (Frontiers in Plant Science, 2024)
Plants employ sophisticated defense mechanisms, including releasing volatile organic compounds, to defend against biotic and abiotic stresses. These compounds play a crucial role in plant defense by attracting natural enemies and facilitating communication between plants to activate defense mechanisms. However, there has been no research on how exposure to these compounds activates defenses in citrus plants. To elucidate the underlying mechanisms governing citrus defensive activation, we conducted a molecular analysis of the rootstock Carrizo citrange [a hybrid of Citrus sinensis × Poncirus trifoliata] in response to defense activation by the volatile (Z)-3-hexenyl propanoate [(Z)-3-HP], utilizing a groundbreaking transcriptomic analysis involving the genomes of both parental species. Our results revealed significant gene expression changes, notably the overexpression of genes related to plant immunity, antioxidant activity, defense against herbivores, and tolerance to abiotic stress. Additionally, plants exposed to (Z)-3-HP repelled several citrus pests, attracted natural predators, and led to diminished performance of two key citrus pests. Significantly, P. trifoliata contributed most notably to the hybrid's gene expression profile in response to (Z)-3-HP. Our study emphasizes the complex molecular basis of volatile-triggered defenses in citrus and highlights the potential of plant volatiles in pest control strategies.